2022
DOI: 10.1007/s41999-022-00667-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing health outcomes between coronary interventions in frail patients aged 75 years or older with acute coronary syndrome: a systematic review

Abstract: Purpose To assess current evidence comparing the impact of available coronary interventions in frail patients aged 75 years or older with different subtypes of acute coronary syndrome (ACS) on health outcomes. Methods Scopus, Embase and PubMed were systematically searched in May 2022 for studies comparing outcomes between coronary interventions in frail older patients with ACS. Studies were excluded if they provided no objective assessment of frailty durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, the authors found a dilution of the efficacy of invasive strategy with increasing age and questioned its value to patients older than 90 years [9].. Recently, Wyk et al published a review from trials since January 1990 to May 2022 that compared clinical outcomes in frail patients with 75 years or older submitted to different coronary interventions; results tend to support invasive treatment, but data was not very robust and with high risk of bias [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors found a dilution of the efficacy of invasive strategy with increasing age and questioned its value to patients older than 90 years [9].. Recently, Wyk et al published a review from trials since January 1990 to May 2022 that compared clinical outcomes in frail patients with 75 years or older submitted to different coronary interventions; results tend to support invasive treatment, but data was not very robust and with high risk of bias [5].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people represent a vulnerable and increasing population presenting with acute coronary syndrome (ACS), and even though advancing age is associated with poor outcomes, these patients tend to receive less evidence-based treatments including coronary angiography [2,3]. Traditionally, older patients were underrepresented in ACS trials [4] and, despite new contemporary trials, there is still a paucity of evidence comparing health outcomes [5].…”
Section: Introductionmentioning
confidence: 99%